Conceptualizing translation revision competence: a pilot study on the 'fairness and tolerance' attitudinal component. - Robert, Isabelle S.; Ureel, Jim J. J.; Remael, Aline; Rigouts Terryn, Ayla (Perspectives: Studies in Translatology, 2018)
Although translation revision plays a crucial role in the production of high-quality translations, research into translation revision competence (TRC) is relatively new and underdeveloped compared with research into translation competence. This article addresses that gap by focusing on the validation of the TRC model developed by Robert, Remael and Ureel. Using questionnaires and revision tasks in a pretest-posttest experimental design, we investigated whether a course on revision and editing affected the degree of fairness and tolerance that participants showed when revising other's translations. Analyses of the results showed that the participants in the experimental group did not make fewer unnecessary changes after taking a course on revision and editing. In addition, the types and sizes of the unnecessary changes that they made were not influenced by taking the revision and editing course. However, when exposed to a revision task without clear instructions and context, participants who had taken the course on revision and editing were significantly less categorical when providing post-treatment answers, even though this behavior was not reflected in their attitudes in the revision tasks. These findings invite further research into the attitudinal component of TRC.